Gossypiboma transduodenal migration causing partial gastric outlet obstruction - Rajesh Sharma; Vishal Bodh; Brij Sharma; R S Jhobta; Rajesh Kumar; Ajay Ahluwalia (Wolters Kluwer Medknow Publications, 2021)
The term "gossypiboma" denotes a mass of cotton that is retained in the body following surgery. It is a rare but serious complication which is seldom reported because of the medicolegal implications. Gossypiboma usually has varied and vague presentation and is also difficult to detect on radiological investigations. It can even remain silent and present years after the operation. We report a case of a 46-year-old female who presented with vague upper abdominal pain associated with postprandial fullness and occasional vomiting. She had a history of open cholecystectomy 16 years ago. Abdominal X-ray and ultrasonogram examination of the abdomen were inconclusive. Her contrast-enhanced computed tomography of the abdomen revealed thickening of the wall of the pyloric antrum with air containing thick-walled structure in relation to the pyloric antrum and the first part of the duodenum possibility of the duodenal diverticulum with inflammatory/neoplastic thickening was suggested. Her esophagogastroduodenoscopy revealed large cotton sponge embedded in the anterior wall of the first part of the duodenum. On exploratory laparotomy, she was found to have a large gossypiboma embedded in the first part of the duodenum with dense adhesions to surrounding structures. Although rare, gossypiboma should be kept in mind as a differential diagnosis in postoperative cases presenting as vague pain even years after the operation.